Analyse & Kritik : Journal of Philosophy and Social Theory (De Gruyter Oldenbourg, 1979)
The Journal is devoted to the fundamental issues of empirical and normative social theory, and is directed at social scientists and social philosophers who combine commitment to political and moral enlightenment with argumentative rigour and conceptual clarity. Published articles develop social theorizing in connection with analytical philosophy and philosophy of science.